Коучинг як інструмент корпоративної бізнес стратегії сталого розвитку агрокомпаній - Крюкова, І. О.; Замлинська, О. В.; Степаненко, С. В. (My University, 2022)
Мета статті –розкрити зміст та характерні ознаки коучингу, як сучасного інструменту реалізації корпоративної бізнес-стратегії сталого розвитку агрокомпаній. В основу проведених досліджень покладено діалектичний метод пізнання процесів і явищ, зокрема, монографічний метод (при виявленні сучасних тенденцій і дослідженні наукових здобутків вітчизняної та зарубіжної науки і практики навчання персоналу),порівняльний (при оцінці рівня витрат та форм навчання персоналу), абстрактно-логічний метод (теоретичні іметодичні узагальнення, обґрунтування висновків), що були використані при визначенні ознак і ролі коучингу як інструменту бізнес-стратегії сталого розвитку агрокомпаній. Досліджено сутність, види та функції коучингу як інструменту управління персоналомкомпаній. Досліджено світовий та вітчизняний досвід навчання персоналу. Визначено роль і характерні ознаки коучингу у системі імплементації принципів сталого розвитку у діяльність агрокомпаній. Обґрунтовано мету, завдання та ключові принципи коучингу як інструменту корпоративної бізнес-стратегії сталого розвитку агрокомпаній. Обґрунтовано авторське тлумачення сутності корпоративної бізнес-стратегії сталого розвитку агробізнесу. Запропонованомодель коучингу у навчанні персоналу за умов імплементації корпоративної бізнес-стратегії сталого розвитку агрокомпаній.Отримані результати дослідження дозволяють удосконалити кадрову політику вітчизняних агрокомпаній на засадах використання переваг коучингу, як перспективного інструменту реалізації бізнес-стратегії сталого розвитку агробізнесу. The purposeof the article is to reveal the content and characteristics of coaching as a modern tool for implementing the corporate business strategy of sustainable development of agricultural companies.The research is based on the dialectical method of cognition of processes and phenomena, in particular, the monographic method (in identifying current trends and research of scientific achievements of domestic and foreign science and practice of personnel training), comparative (in assessing costs and forms of personnel training), abstract-logical method (theoretical and methodological generalizations, substantiation of conclusions), which were used in determining the characteristics and role of coaching as a tool of business strategy for sustainable development of agricultural companies.The essence,types, and functions of coaching as a tool for personnel management of companies are studied. The world and domestic experience of personnel training is studied. The role and characteristic features of coaching in the system of implementationof the principles of sustainable development in the activities of agricultural companies are determined. The purpose, tasks, and key principles ofcoaching as a tool of corporate business strategy of sustainable development of agricultural companies are substantiated.The author's interpretation of the essence of the corporate business strategy of sustainable agribusiness development is substantiated. A model of coaching in staff training is proposed under the conditions of implementation of corporate business strategyof sustainable development of agricultural companies.The results of the study allow to improve the personnel policy of domestic agricultural companies on the basis of using the benefits of coaching as a promising tool for implementing a business strategyfor sustainable development of agribusiness.
Coaching as a tool of corporate business strategy for sustainable development of agricultural companies
Keywords: агрокомпанії; бізнес-стратегія; сталий розвиток; аграрний бізнес; аграрний сектор; персонал; навчання; коучинг; agricultural companies; business strategy; sustainable development; agrarian business; agrarian sector; personnel; training; coaching